1995
DOI: 10.1002/bjs.1800820808
|View full text |Cite
|
Sign up to set email alerts
|

Total mesorectal excision and local recurrence: A study of tumour spread in the mesorectum distal to rectal cancer

Abstract: Total mesorectal excision (TME) appears to be associated with a reduced local recurrence rate following surgery for rectal cancer. Of 20 patients with rectal cancer in whom TME was performed, adenocarcinoma was found in the distal mesorectum in four. Distal mesorectal spread often extended further than intramural spread. Patients with tumour in the distal mesorectum had a worse outcome at 4-year follow-up, a greater risk of local recurrence and an increased frequency of distant metastasis. Distal tumour spread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
127
2
20

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 311 publications
(155 citation statements)
references
References 12 publications
5
127
2
20
Order By: Relevance
“…Disturbance of ORM during operation would predispose local recurrence because the undetected microscopic foci in the mesorectum, especially in ORM were easily left behind in pelvis [4,12,13] . Frequency of CRM involvement after conventional resection was reported up to 27% [2,11,14,15] , compared with 6.5% after TME [16,17] , which is consistent with our findings. The decrease of CRM involvement rates after TME justified the theory: the frequency of microscopic spread in ORM could be very high, and destruction of ORM which often occurred in conventional resection, could easily lead to positive CRM.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Disturbance of ORM during operation would predispose local recurrence because the undetected microscopic foci in the mesorectum, especially in ORM were easily left behind in pelvis [4,12,13] . Frequency of CRM involvement after conventional resection was reported up to 27% [2,11,14,15] , compared with 6.5% after TME [16,17] , which is consistent with our findings. The decrease of CRM involvement rates after TME justified the theory: the frequency of microscopic spread in ORM could be very high, and destruction of ORM which often occurred in conventional resection, could easily lead to positive CRM.…”
Section: Discussionsupporting
confidence: 92%
“…Frequency of discrete tumor cancer spread 3 cm or more from the primary lesions in DMR varied from 0 to 10% of the cases [4,17,[19][20][21][22] , and discontinuous spread in DMR could be found even up to 5 cm beyond the lower margin of the primary tumor [1,6] , some patients with DMR spread had poor prognosis [21][22][23] . The present study showed that four cases with tumor involvement of DMR had the spread within 3 cm of primary mural tumors, with a maximum of 3.0 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor cell deposits within mesorectal lymph nodes have been identified up to 5 cm distal to the inferior aspect of the tumor, emphasizing the need to adhere to the principles of total mesorectal excision and giving rise to the concept of tumor-specific mesorectal excision (mesorectal transection 5 cm distal to the inferior border of the tumor) for more proximal rectal cancers. [24][25][26] In such circumstances, ensuring an adequate distal margin does not jeopardize the potential for sphincter preservation. However, for patients with low-lying tumors treated with total mesorectal excision, the primary concern in the absence of lateral or inguinal lymphatic metastases is distal intramural spread.…”
Section: Introductionmentioning
confidence: 99%
“…Extension of the procedure to the mesorectum is evaluated differently. In 10-20% of patients, tumor dissemination in the mesorectum may reach up to 4.0 cm below the distal margin of the tumor 9,10 . Practically this means that only a mesorectal resection reaching 5.0 cm below the lower margin of the tumor is considered to be a sufficiently radical surgical procedure from an oncological viewpoint.…”
Section: Introductionmentioning
confidence: 99%